Overview of Motivation among Nursing students - Prestasianita Putri; Said Mardijanto; Ika Adelia Susanti (Babali Publisher, 2023)
Introduction: Motivation is a condition that can influence a person's behavior to carry out an activity in achieving goals. Motivation in students of the Nurse profession can influence their performance in implementing the Nurse profession. This study aims to describe the motivation of students in the nursing profession. Method: The research design is non-experimental with a descriptive method. The research population was nursing professional students in the Jember district, with an accidental sampling technique totaling 255 students Result: The results showed that nursing students' motivation had a mean value of 28.17 and a minimum-maximum of 20-36. Indicators of motivation need for achievement with a mean (9.66) and min-max value (7-12), the need for affiliation with a mean value (13.48) and a min-max value (7-16), and the need for power with a mean value (5.02) with min-max value (0-8). Conclusion: The conclusion of the research shows that the motivation of students in the Nursing profession is not optimal. The motivation of students of the Nursing profession can be increased using the surrounding environment, namely family, educational institutions, and places of practice providing support to students of the Nursing profession. The recommendation for nursing professional students is to keep self-motivated in pursuing the ners profession.